Displacement charts for slopes subjected to seismic loads - You, Liangzhi; Michalowski, Radoslaw L. (Elsevier, 1999)
Earthquake events in recent years have brought about renewed interest in analyses of slopes subjected to seismic loads. These loads have been accounted for traditionally by using quasi-static loads. Such analyses do not provide any information about permanent displacements, and they neglect the history of seismic shaking. The analysis presented in this note is based on the rigid block displacement technique. A rotational mechanism of slope failure, caused by horizontal shaking, is considered. Yield accelerations are calculated for uniform slopes, and irreversible displacements are calculated for different earthquake records. The displacements can be represented as the product of a coefficient characteristic of a given collapse mechanism and a double time integral of an earthquake acceleration record. Charts are produced to make the application of the results effortless.